COVID-19 Vaccination and Communicable Disease Testing Services' Integration Within a Syringe Services Program: A Program Brief. (12th May 2022) - Heidari, Omeid; Meyer, Diane; O'Conor, Katie J.; Cargill, Victoria; Patch, Michelle; Farley, Jason E.
Abstract: People who inject drugs often have a higher prevalence of risk factors associated with coronavirus disease 2019 (COVID-19) infection and associated morbidity and mortality, compounded by challenges in health care access. This increased vulnerability underscores the critical need to prioritize people who inject drug in ongoing COVID-19 vaccination efforts. Co-location of syringe services, COVID-19 vaccination services, and other communicable disease testing has proved an effective model to provide necessary interventions without creating additional barriers. Here, we describe a partnership between the Baltimore City Health Department, Johns Hopkins Mobile Vaccine Unit, and the Center for Infectious Disease and Nursing Innovation at the Johns Hopkins School of Nursing to provide COVID-19 vaccination, HIV and sexually transmitted infection testing, wound care, and linkage to care services co-located with a long-running syringe services program. We describe the services offered by each partner and lessons learned from this community-based co-location of services initiative.